2012
DOI: 10.1007/s10495-012-0772-8
|View full text |Cite
|
Sign up to set email alerts
|

p53 acetylation enhances Taxol-induced apoptosis in human cancer cells

Abstract: Microtubule inhibitors (MTIs) such as Taxol have been used for treating various malignant tumors. Although MTIs have been known to induce cell death through mitotic arrest, other mechanisms can operate in MTI-induced cell death. Especially, the role of p53 in this process has been controversial for a long time. Here we investigated the function of p53 in Taxol-induced apoptosis using p53 wild type and p53 null cancer cell lines. p53 was upregulated upon Taxol treatment in p53 wild type cells and deletion of p5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 33 publications
0
27
0
Order By: Relevance
“…p53 can also directly activate pro-apoptotic proteins such as Bax, which can also inactivate anti-apoptotic proteins such as Bcl-2 [45]. Therefore, p53 is a promising target for cancer treatment, and it has been demonstrated that up-regulating the expression of p53 is beneficial for treatment of cancers [46,47].Bcl-2 family proteins including Bax, Bcl-2 and others play pivotal roles in intrinsic apoptosis and are recognized as the first regulatory step for inducing mitochondrial apoptosis [48]. In our investigation, PTA significantly up-regulated tumor tissue expression of p53 and Bax proteins but down-regulated Bcl-2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…p53 can also directly activate pro-apoptotic proteins such as Bax, which can also inactivate anti-apoptotic proteins such as Bcl-2 [45]. Therefore, p53 is a promising target for cancer treatment, and it has been demonstrated that up-regulating the expression of p53 is beneficial for treatment of cancers [46,47].Bcl-2 family proteins including Bax, Bcl-2 and others play pivotal roles in intrinsic apoptosis and are recognized as the first regulatory step for inducing mitochondrial apoptosis [48]. In our investigation, PTA significantly up-regulated tumor tissue expression of p53 and Bax proteins but down-regulated Bcl-2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, acetylation appears to be essential for p53-mediated growth arrest and apoptosis [257]. Acetylation is also required for p53-mediated induction of apoptosis through HDAC-inhibitors [417] and through the microtubule inhibitor Taxol [418]. The acetylation of p53 by MOF or Tip60 on K120 is important for its activation of pro-apoptotic genes (reviewed in [419]).…”
Section: Pcafmentioning
confidence: 99%
“…DNA-damaging agents induce apoptosis in cancer cells by activating p53 through the ATM pathway (48). Taxanes also induce p53 via post-transcriptional modifications that increase both its level and activity (5). To date, strategies directed at activating p53 in tumors have largely focused on targeting wild-type p53, rather than the mutated p53 present in a significant percentage of most solid tumors.…”
Section: Discussionmentioning
confidence: 99%
“…This induces a prolonged activation of the mitotic spindle checkpoint and mitotic arrest followed by mitotic slippage and induction of apoptosis (5). Although considered cytotoxic, they are in fact cytostatic, with the arrest triggering cell death (6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation